Exploring preliminary structural relationships and mitochondrial targeting of fac-[MI(CO)3]-bis(diarylphosphino)alkylamine complexes (M = 99Tc, Re). (17th November 2021) - Kama, Dumisani V.; Frei, Angelo; Schutte-Smith, Marietjie; Brink, Alice; Swart, Chantel; Braband, Henrik; Alberto, Roger; Roodt, Andreas
Abstract : Preliminary structural relationships in fac -[M I (CO)3 ]-bis(diarylphosphino)alkylamine complexes (M = 99 Tc, Re), antimicrobial and mitochondrial targeting are reported. Abstract : Two bidentate PNP ligands N, N -bis(di- p -tolylphosphino)cyclohexylamine (Cy- p TolPNP) (1 ) and N, N -bis(di- p -tolylphosphino)cyclobutylamine (Cb- p TolPNP) (2 ) were synthesized and crystallized. Coordination to the fac -[M I (CO)3 ] + core (M = Re, 99 Tc) yielded fac -[Re(Cy- p TolPNP)(CO)3 Br] (1A ), fac -[ 99 Tc(Cy- p TolPNP)(CO)3 Cl] (1B ), fac -[Re(Cb- p TolPNP)(CO)3 Br] (2A ) and fac -[ 99 Tc(Cb- p TolPNP)(CO)3 Cl] (2B ) in relatively good yields (56 to 86%): The structures of 1, 2, 1A and 1B were studied by single crystal X-ray crystallography. Preliminary mitochondrial/antimicrobial evaluation of the free ligand ( N, N -bis(di- p -tolylphosphino)-cyclohexylamine) (1 ) and its respective fac -[Re(CO)3 ] + (1A ) complex indicates that neither the free ligand nor the complex was active against selected fungi Eremothecium ashbyii and Nadsonia fulvescens . In addition, all four compounds were found to have no activity against Gram-positive and Gram-negative bacterial species. These biological results are essential to the understanding of how these types of complexes behave and show they are perfectly stable in the evaluated bio-environments. The results also indicate that these ligands and complexes may present themselves as excellent models for radiotoxicity studies using technetium-99m, but more specifically, rhenium Re-186 and Re-188.